Respuesta :

MsRay

Answer:

3(m - 3) = 3m - 9

0 = 0

m = infinitely many solutions

Step-by-step explanation:

In the given equation, there is a distribution of the factor of 3 to the expression 'm - 3' on the left side and the expression '3m - 9' on the right.  When you distribute the '3', you get: 3m - 9. Since 3m - 9 is equal to 3m - 9, the constants and variables would each cancel out by inverse operations and you would be left with 0 = 0, which indicates an equation with infinitely many solutions.

ACCESS MORE